Peer Computer-Mediated Corrective Feedback In Essay Writing Performed By University Students - Mellinda Putri Berliana (Jetlal, 2023)
The purpose of this study is to investigate how university students perform peer computer-mediated corrective feedback. This study is conducted qualitatively through the students' essay analysis and interview to briefly overview how the students perform peer computer-mediated corrective feedback. The sixteen participants, who have conducted peer computer-mediated corrective feedback in an exemplification writing class, are from one of the state universities in Surabaya. The study's results revealed that not all types of peer computer-mediated corrective feedback were conducted by the students. Most of the students give feedback starting from the aspects they believe they can do. They start it by reading the whole essay and moving on to the aspects of writing they check. The students who have less confidence in a particular aspect of writing do not provide the aspect of writing they do not believe they are able to. This leads to the students using another software to assist them in giving feedback to their peers. Moreover, the students are depending on their lecturer's instruction in giving feedback thus the role of lecturers in giving feedback literacy is important in purpose to increase the student's productivity in giving feedback. In conclusion, this study suggests the students' feedback literacy needs to be boosted through their lecturers. The findings highlight the way students perform peer computer-mediated corrective feedback.